A comparative study of intrapersonal skills - Khalida Rauf , Zeenat Ismail (Pakistan Journal of Psychology, 2011)
The purpose of the present research was to determine the effect of learning disabilities on Intrapersonal skills. It is hypothesized that the non learning disabled students will have higher Intrapersonal skills than the learning disabled students. The sample comprised 80 learning disabled and 80 non learning disabled students. The learning disabled group includes 51 boys and 29 girls. The non learning disabled group includes 41boys and 39 girls. The learning disabled group was randomly selected from remedial schools and schools with screening psychologists and psychological clinics. The non learning disabled group was randomly selected from normal schools of upper middle and upper socioeconomic strata. In order to gain information regarding age, sex, qualification, parents, income and any other psychological problem Demographic Variable Form, and in order to measure the Intrapersonal skills the Intrapersonal subscale of the Bar-On Emotional Quotient Inventory, Youth Version was administered. For statistical analyses of the data ttest was applied. Findings suggest insignificant difference in the level of Intrapersonal skills between the two groups p>.05 level